POLA PERILAKU SEHAT DAN MODEL PELAYANAN KESEHATAN REMAJA - Endang Ekowarni (Faculty of Psychology, Universitas Gadjah Mada, 2001)
Behavioral health is one of the many aspects in youth's life. A pattern of behavior which is more oriented to peer group activities often becomes a factor draw teenagers to a behavior that is risky to health. The Subject of the research consist of the teen patient and the doctors of a chosen hospital. A conclusion has been made that teens do have a behavioral pattern of health which is less gainful as a result of thinking pattern and amistaken undertanding of health, diseases, healthy life pattern, drug abuse, and premarital sex. Doctors have a positive perception towards their teen patients.Generally, doctors have good understanding to the needs and the characteristics of teenagers and have an opinion that teens need a special service which is divided into promotive, preventive, curative, and rehabilitative programs.